The teaching of process writing skills with special reference to brainstorming and mind mapping at the upper secondary level in Singapore school - Abduyah Yaakub (2008)
The aim of the report is to determine whether the use of the process writing with special emphasis on brainstorming and mind mapping helps to improve the writing skills of Upper Secondary pupils in a neighbourhood school.